The Influence of E-Commerce and Digital Marketing on Startupreneur Performance Using PLS-SEM - Lista Meria; Andriyansah; Priandito; Ninda Lutfiani; Ridan Ahsani Te Awhina (CORISINTA, 2025)
Startupreneurs increasingly rely on technology to manage their business, especially in using e-commerce applications and digital business marketing strategies. This research investigates the influence of e-commerce applications and digital business marketing on startup entrepreneur performance. The research method used is an online survey of 150 startup entrepreneurs in Indonesia who are active in various industries. Data was collected using a questionnaire that measures the level of use of e-commerce applications, digital business marketing practices, and startupreneur performance based on factors such as revenue growth, customer satisfaction, and market visibility. The results of the analysis show that the use of e-commerce applications has a significant favourable influence on startupreneur performance. Startupreneurs who actively use e-commerce applications tend to have higher revenue growth and better levels of customer satisfaction. Additionally, digital business marketing strategies were also found to positively affect startup business performance, especially in increasing market visibility and broader market penetration. This research makes an essential contribution to understanding how technology and digital marketing strategies can help improve startupreneur performance. The practical implication of this research is the importance of integrating e-commerce applications and digital business marketing in startup business growth strategies. Steps to improve startupreneur performance could involve investing in digital technology and improving skills in managing online marketing strategies.